Dynamics of the papaya meleira virus complex during the development of papaya (Carica papaya L.) - Araujo, Marlonni Maurastoni (2021)
Among the most serious virus-incited diseases in papaya production is papaya sticky disease (PSD). This disease was first reported in Brazil in 1993, associated with a double-stranded RNA virus, called papaya meleira virus (PMeV). Since then, progress has been made in the knowledge of the disease dispersion in the field, the etiological agent characterization, and its interactions with papaya. However, in 2016, the papaya meleira virus 2 (PMeV2), with a positive single-stranded RNA genome, was also identified in diseased plants, imposing a rethinking of the pathosystem. Therefore, in this work, we critically evaluate the latest findings on PSD and the last 30 years of research done to understand its dispersion in the field. We show that leafhopper and whitefly species need to be better studied as potential vectors of the PSD-associated viruses in Brazil now that more sensitive molecular diagnostic techniques are available. Nevertheless, we developed a multiplex RT-PCR (mPCR) technique capable of detecting both viruses in a single reaction from pre-flowering plant samples, which is a useful tool for the early diagnosis of PSD. Here we show that laticifers of the main vein of papaya sticky diseased leaves are the preferential infection site of PMeV and PMeV2. We also show that the PMeV capsid is composed of two major polypeptides with overlapping sequences. A central fragment of these polypeptides (aa 321-670) interacts with the 50S ribosomal protein L17 (RPL17), which we speculate as an important player in virus accumulation. Overall, this thesis discusses PSD in three main spheres: the biology of the etiological agent and its interaction with the host, the spread of the disease in the field, and the development of technologies for its management.